P0732DOES KIDNEY FUNCTION INFLUENCE PLASMA ADIPONECTIN CONCENTRATION IN ELDERLY CAUCASIANS?. (6th June 2020) - Adamczak, Marcin; Dudzicz, Sylwia; Chudek, Jerzy; Zejda, Jan; Zdrojewski, Tomasz; Wiecek, Andrzej Jan
Abstract: Background and Aims: Adiponectin is a hormone produced almost exclusively by the adipose tissue with vaso-protective activity and mostly metabolized in the kidneys. Glomerular filtration rate (GFR) is declining with age in elderly subjects and therefore it is expected to be followed by accumulation of adiponectin in the circulation. The aim of this study was to assess the plasma concentration of adiponectin in relation to GFR in the older population-based on the PolSenior study cohort. Method: The PolSenior study was a multicenter cross-sectional study which assessed the health status of older adults in Poland. In 3913 subjects aged 65 years or above (2041 male and 1872 female, BMI 28.1±5.1 kg/m 2, mean age 79±9 years) plasma adiponectin concentration (ELISA; B-Bridge International) was measured. GFR was estimated using a short MDRD formula. All results are presented as means with standard deviations. Results: In studied subjects eGFR was 76 ml/min/1.73 m 2 . eGFR below 60 ml/min/1.73 m 2 was observed in 842 (22%) subjects. Plasma concentration of adiponectin was 11.9±6.4 µg/ml. In subjects with eGFR < 60 ml/min/1.73 m 2 significantly higher plasma adiponectin concentrations were observed compared to subjects with eGFR ≥ 60 ml/min/1.73 m 2 (12.5±6.7 vs. 11.8±6.3 respectively, p=0.01). Plasma adiponectin concentration depends strongly on BMI (R= -0.28; p<0.001) and marginally on the kidney function (R=-0.05; p=0.005). Multivariate regression analysis including plasma adiponectin concentration, BMI, eGFR, occurrence of diabetes mellitus and hypertension, showed that BMI and prevalence of diabetes (b=-0.24, p<0.001, b=-0.11, p<0.0001, respectively) but not eGFR explain variability of plasma adiponectin concentration. Conclusion: Plasma adiponectin concentration is only slightly affected by kidney function in elderly Caucasians from the PolSenior study.